Strategic management competitiveness and globalization - Hitt, Michael A.; Ireland, R. Duane; Hoskisson, Robert E. (Thomson / South-Western, 2007)
This edition consists of 35 cases representing a myriad of strategy topics and types of firms and industries. The authors have meticulously reviewed hundreds of cases to create this package.